(untitled) (Modern education and development, 2025)
This research article explores the uneven effects of automation on low- and high-skill workers, focusing on how technological advancements impact different segments of the labor market. The paper is structured to analyze the implications of automation in terms of both opportunities and challenges for workers at various skill levels, with a particular emphasis on economic inequality, job displacement, and future trends.